RUANG EKSPRESI DAN APRESIASI BAGI MUSISI JALANAN DI KAWASAN SENEN, JAKARTA PUSAT - Yuono, Glorius Timoty; Hadiwono, Alvin (Jurusan Arsitektur dan Perencanaan, 2024)
The city of Jakarta has a profession called Street Musician. However, many streets are affected by economic pressures in the development of the city of Jakarta. Street musicians have no platform and are starting to be neglected. There is a need for space to accommodate the activities of street musicians in the city of Jakarta. The aim is to help develop quality musicians and entertainment spaces for the city of Jakarta, where currently music is embedded in everyday lifestyle. Based on data collected through interviews and observations, there is a formation process that represents the reality of the perpetrators, namely street musicians themselves. From various kinds of phenomena, facts and rules, the author can use them as a reference to define space in accordance with existing discourse. There are several factors that influence a musician's performance, including sound factors, lighting factors, performance space, and audience and circulation space. If these factors are taken into account properly, they can support musicians in presenting works that visitors can enjoy well too. If there is space for the musicians and the audience, they can enjoy the musicians' expressions comfortably so that they will naturally appreciate the musicians' performances. These spaces need to be combined well because they have different identities, namely spatial (architecture) and musical. Pasar Senen, which used to have a rich artistic culture, will be re-emerged as a space for musicians to express themselves, creating spaces for musicians to gather and improving the quality of musicians at Pasar Senen and in its surroundings. Keywords: appreciation space; expression space; street musicians Abstrak Kota Jakarta memiliki salah satu profesi yang di sebut Musisi Jalanan. Namun musisi jalanan terkena dampak tekanan ekonomi dalam perkembangan kota Jakarta. Musisi Jalanan tidak memiliki wadah dan mulai terabaikan. Perlu adanya ruang untuk mewadahi aktifitas dari musisi jalanan di kota jakarta. Tujuannya adalah untuk membantu mengembangkan kualitas musisi dan ruang hiburan bagi kota Jakarta, dimana saati ini musik sudah melekat dalam gaya hidup sehari-hari. Berdasarkan data-data yang terkumpul melalui wawancara dan pengamatan, terdapat proses pembentukan yang merepresentasikan realitas pelaku yaitu musisi jalanan sendiri. Dari berbagai macam fenomena, fakta dan aturan, penulis dapat menjadikannya sebagai acuan untuk mendefinisikan ruang yang sesuai dengan wacana yang ada. Terdapat beberapa faktor yang berpengaruh pada penampilan musisi, diantaranya adalah fakor suara, faktor pencahayaan, ruang penampilan, dan ruang penonton dan sirkulasi. Faktor-faktor tersebut apabila di perhitungkan dengan baik dapat mendukung musisi menampilkan karya yang dapat dinikmati pengunjung dengan baik juga. Apabila ruang musisi dan penonton terpenuhi mereka dapat menikmati ekspresi musisi dengan nyaman sehingga dengan sendirinya mereka akan memberikan apresiasi dari penampilan musisi. Ruang-ruang ini perlu dikombinasikan dengan baik karena memiliki identitas yang berbeda yaitu keruangan (Arsitektur) dan musik. Pasar senen yang dulunya memiliki kekayaan budaya seni, akan dimunculkan kembali sebagai ruang untuk musisi berekspresi, menciptakan ruang-ruang untuk para musisi berkumpul dan meningkatkan kualitas musisi di Pasar Senen maupun di sekitarnya.